Do Experiences and Entrepreneur Motivation Influence Success and Failure Students’ Business? - Kuswanto Kuswanto; May Maemunah; Refnida Refnida (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
This study aims to determine the effect of entrepreneurial experience and motivation on the success of students of the Jambi University Entrepreneurship Student Program (ESP). This research uses the ex post facto method. The subjects in this study were students who received ESP Program funding in 2018, totaling 50 business groups. Data were analyzed descriptively and quantitatively using multiple regression. Statistical test results show the accuracy of the model as a predictor of 44 percent. The experience of entrepreneurship has a positive and significant effect on the success of student ventures. Entrepreneurial motivation does not affect the success of student ventures. Simultaneously entrepreneur experience and entrepreneurial motivation have a positive and significant effect on the success of student ventures. The results of this study recommend that ESP program managers be more selective in determining students who receive start-up business funds to be more productive and efficient. Future research should examine other factors that influence the success of student efforts to produce more comprehensive studies as a basis for policy.